Nonquasineutral current structures in plasmas with a zero net current - Gordeev, A.V. (Вопросы атомной науки и техники, 2006)
A nonquasineutral vortex structure with a zero net current is described that arises as a result of electron drift in
crossed magnetic and electric fields, the latter being produced by charge separation on a spatial scale of about the
magnetic Debye radius. In such a structure with radius r ~ rB, the magnetic field maintained by a
drift current on the order of the electron Alfven current. The system with closed current that is considered in the present paper can also serve as a model of hot spots in the channel of a Z-pinch.